ACPA Alleviates Bleomycin-Induced Pulmonary Fibrosis by Inhibiting TGF-β-Smad2/3 Signaling-Mediated Lung Fibroblast Activation - Chen, Dongxin; Tang, Huirong; Jiang, Hongchao; Sun, Lei; Zhao, Wenjuan; Qian, Feng (Frontiers in Pharmacology, 2022)
Pulmonary fibrosis is a group of life-threatening diseases with limited therapeutic options. The involvement of cannabinoid type 1 receptors (CB1R) has been indicated in fibrotic diseases, but whether or not the activation of CB1R can be a benefit for fibrosis treatment is controversial. In this study, we investigated the effects of arachidonoylcyclopropylamide (ACPA), as a selective CB1R agonist, on bleomycin (BLM)-induced pulmonary fibrosis. We showed that ACPA treatment significantly improved the survival rate of BLM-treated mice, alleviated BLM-induced pulmonary fibrosis, and inhibited the expressions of extracellular matrix (ECM) markers, such as collagen, fibronectin, and α-SMA. The enhanced expressions of ECM markers in transforming growth factor-beta (TGF-β)-challenged primary lung fibroblasts isolated from mouse lung tissues were inhibited by ACPA treatment in a dose-dependent manner, and the fibroblast migration triggered by TGF-β was dose-dependently diminished after ACPA administration. Moreover, the increased mRNA levels of CB1R were observed in both lung fibroblasts of BLM-induced fibrotic mice in vivo and TGF-β-challenged primary lung fibroblasts in vitro. CB1R-specific agonist ACPA significantly diminished the activation of TGF-β–Smad2/3 signaling, i.e., the levels of p-Smad2 and p-Smad3, and decreased the expressions of downstream effector proteins including slug and snail, which regulate ECM production, in TGF-β-challenged primary lung fibroblasts. Collectively, these findings demonstrated that CB1R-specific agonist ACPA exhibited antifibrotic efficacy in both in vitro and in vivo models of pulmonary fibrosis, revealing a novel anti-fibrosis approach to fibroblast-selective inhibition of TGF-β-Smad2/3 signaling by targeting CB1R.